SOURCE‐ROCK MATURITY, HYDROCARBON POTENTIAL AND OIL – SOURCE‐ROCK CORRELATION IN WELL SHORISH‐1, ERBIL PROVINCE, KURDISTAN REGION, IRAQ. (October 2015) - Sachsenhofer, R. F.; Bechtel, A.; Gratzer, R.; Rainer, T. M.
<x xml:space="preserve">Abstract</x> The Shorish‐1 exploration well is located in Erbil Province in the Kurdistan region of Iraq, on the outskirts of Erbil City near the dividing line between the Low Folded and High Folded Zones of the Zagros foldbelt. The well penetrated rocks which are between Miocene and Late Triassic in age. The depositional environment, source potential and maturity of organic‐rich intervals within the well succession were investigated using 38 cuttings samples. All samples were analysed for bulk geochemical parameters (i.e. total organic carbon, total carbon, sulphur, Rock‐Eval). A subset of 13 samples was selected for biomarker analysis, pyrolysis – gas chromatography and isotope investigations. In addition non‐commercial oil and oil impregnations were investigated for oil‐source correlations. Source rocks occur in the Jurassic Sargelu and Naokelekan Formations and the lowermost Cretaceous Chia Gara Formation. Analytical results suggest that these source rocks were deposited in a carbonate‐rich, anoxic environment in an intrashelf basin setting with free H2S in the water column. Oxygen‐depleted conditions were favoured by salinity stratification. The average preserved TOC contents of the 100 m thick Sargelu Formation and the 25 m thick Naokelekan Formation are 2.2% and 4.6%, respectively. The TOC content of the Chia Gara Formation decreases upwards and averages 3.2% within its lower 40 m. Very high sulphur contents suggest the presence of kerogen Type II‐S, and that all the formations have generated sulphur‐rich hydrocarbons at relatively low maturities. In contrast to the oil impregnations within Jurassic strata, the oil and the oil impregnations within Cretaceous rocks are heavily biodegraded. Oil biomarker and isotope data indicate generation from the above‐mentioned Jurassic and Cretaceous source rock formations. As a result, generation from Triassic and Paleogene rocks can be excluded or is of negligible significance. Numerical models show that hydrocarbon generation rates from the Sargelu, Naokelekan and Chia Gara Formations peaked firstly at about 55 Ma (Paleocene/Eocene) and then again at 5 Ma before present (late Miocene/Pliocene). The first peak resulted from increased Paleocene subsidence, and the second peak was related to deep late Miocene/Pliocene burial. Hydrocarbon generation ceased during Recent uplift, during which ∼2000 m of the Late Neogene succession was eroded.